(untitled) (Journal of Governance and Development (JGD), 2023)
This paper is basically an application of the famous elite perspective to the Nigerian government and politics to test whether it is a theory that can be confirmed or infirmed. The observable phenomenon which is similar to virtually all regions and climes of the world is the emergence of very few people circulating in the political space over time. From pre-colonial, to colonial and post-colonial Nigerian state, a number of elites from diverse sectors of the society – the military, politicians, civil society, business tycoons, religious leaders and traditional elites kept circulating in the political firmament of Nigeria. The paper is a confirmation of the elite theory paradigm or construct to the understanding of Nigerian government and politics. The paper however noted that if nothing changes the required leap from a developing status of Nigeria as a country to developed one may take time after all more so that the country needs new thinking and perspectives to be able to adapt to modern technological era. The paper infers that there is an imperatival need to opening up of the political space to accommodate vibrant youths and new set of elites that can drive the polity to a greater height with new innovative thinking.